PENGARUH FASILITAS PERMATA SKIN CARETERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT UMUM PURWA HUSADA PURWOREJO (STIE Rajawali Purworejo, 2018)
This study aims to determine the relationship between Permata Skin Care facilities on patient satisfaction at Purwa Husada General Hospital. The analytical tool used is with tools SPSS 18.0 for windows. The research method used in collecting data is, multiple regression, coefficient of determination, t test, and test F. From the calculation of multiple regression obtained regression equation Y =14,194 + 0,170 XI + 0,173X2. Hypothesis testing resulted tcount of facial care (X1) is smaller than ttable value (1,028 <1,703) so hypothesis stating that there is positive and significant influence between facial care variable with patient satisfaction rejected, value of beauty product count (X2) more small from the ttable (1,257 <1,703) so the hypothesis that there is a positive and significant influence between beauty product variables with patient satisfaction in rejection. Testing Anova yield F number counted 1,792 by using confidence level 95% (ɑ = 0,05) obtained Ftabel 3,35. So Fhitung smaller than Ftabel (1,792 <3,35), hence can beinterpreted that facial care and beauty product variables simultaneously have no effect to patient satisfaction.